Solid-phase trace element contents, Mo isotopes and pore-water trace element concentrations of sediment cores from IODP Hole 370-C0023A - Jingbo Nan; Man-Yin Tsang; Jie Li; Male Köster; Susann Henkel; Fanyu Lin; Weiqi Yao (PANGAEA, 2023)
The dataset includes solid-phase and porewater trace elements data of sediment cores from Site C0023 (Hole A) that was recovered during International Ocean Discovery Program (IODP) Expedition 370 in the Nankai Trough offshore Japan in the Pacific Ocean (Drilling vessel Chikyu). Site C0023 was established on 17 September 2016. Coring terminated on 3 November 2016. Solid-phase trace elements data include bulk molybdenum (Mo), uranium (U), vanadium (V), and rare earth elements (REEs) contents, and Mo isotopes. Trace element analyses were performed using a Thermo Fisher iCAPQ ICP-MS equipped with a ASX560 AutoSampler. Approximately 50 mg of each dry sediment powder was dissolved in Teflon bomb with the double-distilled concentrated HNO3-HF (1:1) mixture. The dissolution was maintained in an oven at 185°C for 3 days and then dried down to evaporate HF. The residues were re-dissolved with double-distilled concentrated HNO3 followed by the HNO3-H2O (1:1) mixture, and dried again. After that, the sample was dissolved in the final 3ml 2N HNO3 stock solution. Finally, the sample solution is diluted by 1000 times with 2.5% HNO3 and 10ppb Rh internal spikes. The standard GBW07316 was used as a reference. Internal spikes and external monitors were used to correct instrument drift mass bios. The ICP-MS procedure for trace element analyses is based on the protocol developed by Eggins et al. (1997, doi:10.1016/S0009-2541(96)00100-3). The Mo-isotope composition were analyzed by a Thermo-Fisher Scientific Neptune-Plus multi-collector inductively coupled plasma mass spectrometer (MC-ICP-MS) using the double-spike method. About 0.02-0.05g whole-rock powders were weighed and combined with appropriate amounts of a 97Mo-100Mo double spike within a pre-cleaned 15 mL PFA beaker. The sample was then dissolved using 1 mL HNO3 and 2 mL HF at 140 ? for 2 days before being dried at 120 ? and re-dissolved in 4 mL of a 1 M HCl-0.3 M HF mixture for column separation. Molybdenum was separated and purified using an N-benzoyl-N-phenyl hydroxylamine extraction chromatographic resin with the approaches outlined in Li et al. (2014, doi:10.1111/j.1751-908X.2013.00279.x). Pore water trace elements data include Mo, U, V, and nickel (Ni). The pore water was collected during IODP Expedition 370 as described in the Expedition 370 Methods by Heuer et al. (2017;doi:10.14379/iodp.proc.370.103.201). The trace elements were measured in untreated (original) in acidified pore-water samples. The inductively coupled plasma-mass spectrometry (ICP-MS, Element2, Thermo Fisher Scientific Inc.) is equipped with an ESI Apex-Q desolvating system to increase the sensitivity.